Transcatheter closure of perimembranous ventricular septal defects in elderly patients and risk factors of postoperative arrhythmias - Wang, Jianming; Zhu, Xianyang; Geng, Jingsong; Wang, Qiguang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe mid- and long-term safety and efficacy of perimembranous ventricular septal defect (pmVSD) closure and the risk factors of postoperative arrhythmias in elderly patients were not known.MethodsFrom January 2009 to June 2023, 59 pmVSD elderly patients aged over 60 years were treated through transcatheter intervention. The results and complications of the closure were evaluated by electrocardiography (ECG) and transthoracic echocardiography (TTE) immediately and 1 day after the procedure. TTE was done 1, 3, 6, 12 m, and as a follow up annually.ResultsInterventional closure was successful in all 59 patients. The immediate residual shunt rate was 18.6%. Postoperative arrhythmias occurred in 37 patients (62.7%, 37/59), including severe complications of complete atrioventricular block (cAVB) and implantation of permanent pacemakers in 2 patients (3.4%, 2/59). During the follow-up period, 2 deaths were recorded (due to lung cancer and acute myocardial infarction), and there were no serious complications, such as infective endocarditis, occluder embolism or valve regurgitation requiring surgical treatment. Older age (P = 0.006, OR = 1.723, 95% CI: 1.613–1.845) and the occluder size ratio (d-value of ventricular septal defect, dVSD/Body Surface Area, BSA) (P = 0.002, OR = 1.231, 95% CI: 1.182–1.283) were found to be independent risk factors for a high incidence of arrhythmias after occlusion.ConclusionsElderly patients with pmVSD aged over 60 years have a great risk of arrhythmias after transcatheter closure. Older age and the occluder size ratio are associated with short-term postoperative arrhythmias.